2023
DOI: 10.1080/07853890.2023.2295435
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose level and serum lipid profiles among people living with HIV on dolutegravir-based versus efavirenz-based cART; a comparative cross-sectional study

Mohammed Jemal,
Tewodros Shibabaw Molla,
Markeshaw Tiruneh G. Medhin
et al.

Abstract: Background Antiretroviral therapy-linked metabolic abnormalities have become a growing concern among people living with HIV. There is limited data regarding the effects of dolutegravir-based treatment on blood glucose levels and serum lipid profiles in people living with HIV in Ethiopia. Thus, this study aimed to assess blood glucose levels and serum lipid profiles among people living with HIV on dolutegravir-based versus efavirenz-based therapy. Method and materials An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This is consistent with a study from Kampala, Uganda 73 and USA, 74 and Ethiopia. 75,76 Hyperglycemia in obese patients is due to increased release of free fatty acids to activate protein kinases and pro-inflammatory cytokines like interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) released from adipose tissue impair insulin signalling and causes insulin resistance. 77,78 In addition, our study demonstrated that patients on the DTG-based ART regimen were 4.6 times more likely to have hyperglycemia than patients on the ATV/r-based ART regimen.…”
mentioning
confidence: 99%
“…This is consistent with a study from Kampala, Uganda 73 and USA, 74 and Ethiopia. 75,76 Hyperglycemia in obese patients is due to increased release of free fatty acids to activate protein kinases and pro-inflammatory cytokines like interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) released from adipose tissue impair insulin signalling and causes insulin resistance. 77,78 In addition, our study demonstrated that patients on the DTG-based ART regimen were 4.6 times more likely to have hyperglycemia than patients on the ATV/r-based ART regimen.…”
mentioning
confidence: 99%